Narrative Analysis of the Link between Modern Medicine and Traditional Medicine in Africa: A Case of Mental Health in Uganda - Abbo, C.; Odokonyero, R.; Emilio, Ovuga (Brain Research Bulletin, 2018)
Traditional Medicine Practices (TMP) which are premised on indigenous knowledge and experiences within a local context of the culture and environment, are common place in low income countries. In Africa and in Uganda specifically, nearly 80% of the Ugandan population relies on TMP for the care of their mental health but they also use Modern Medicine. There are areas of departure between Traditional and Modern Medical practices in Africa that have been cited. What has attracted less research attention, are the areas of convergence. Objective: This paper aims to critically examine the link between Modern Medicine and Traditional Healing Practices in Africa, citing Uganda as case example. Method: A Narrative literature review with critical element assessment was undertaken to identify documented points of departure, areas of common practice, and ways in which the two models can co-exist and work together through a carefully thought out integration. Results: Points of departure between Modern Medicine and Traditional Medicine Practices are philosophical underpinnings of both practices, training of practitioners, and methods and ethics of work. Common areas of practice include human rights perspective, descriptions of mental illnesses, clinical diagnostic practice, particularly severer forms, intellectual property rights, and cross prescriptions. Exhibiting cultural humility on the side of the modern medicine practitioners is one of the ways to work together with TMPs. Conclusion: Points of departure are more documented and explicit and overshadow areas of common practice while the links between the two are mainly implicit but sadly unrecognized. Mental disorders are disorders of the brain and in neuroscience; the brain is culturally and socially constructed. Sociocultural issues therefore cannot be divorced from disorders of the brain and their management. For better patient outcome and patient-centered approach of care, it is necessary to acknowledge and enhance the links in teaching, clinical and policy level and carry out research on how the links could be improved.
Keywords: Traditional Healing; Traditional Medicine; Modern Medicine; Mental Health; Uganda; Traditional Healing Practices; Modern Medicine Practices